(untitled) (Ustozlar uchun, 2026)
Computer-Assisted Language Learning (CALL) has become an essential component of modern language education. It provides learners with opportunities to develop their language skills through digital technologies such as computers, mobile applications, and online platforms. CALL supports the improvement of four main language skills: listening, speaking, reading, and writing. The use of multimedia resources, interactive exercises, and online communication tools increases students’ motivation and engagement in the learning process. This article discusses the role of CALL in developing language skills and highlights its importance in modern language teaching.